Myths and Facts about Placebo - Hans-Joachim Kremer (Journal of Pharmacy and Nutrition Sciences, 2016)
Many patients, physicians, and sometimes even academics have questionable perceptions of placebo and the so-called placebo effect, Many believe that placebo have its own effects. Although psychological aspects, namely expectations of patients or the persuasive power of the physicians, might sometimes be substantial, such aspects may have little or even no relevance in other situation where placebo control is essential nevertheless. Even in settings where psychological effects should be envisaged, their extent is usually highly variable, indicating that other factors might still exceed the importance of psychological effects. Placebo is defined in US regulations as an inactive preparation designed to resemble the test drug as far as possible. This means that placebo itself cannot be effective. If it would, its correctness is challenged and it should be replaced if still possible. And as placebo is not effective, it can also not have secondary effects, vulgo side effects. Placebo is always used for two reasons: To control bias and to provide the reasonably largest delta, i.e. the difference between two treatments. Placebo should never be interpreted as being able to cause effects.